2019
DOI: 10.1093/nar/gkz816
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase 3 controls a transcriptional network required for B cell maturation

Abstract: Histone deacetylase 3 (Hdac3) is a target of the FDA approved HDAC inhibitors, which are used for the treatment of lymphoid malignancies. Here, we used Cd19-Cre to conditionally delete Hdac3 to define its role in germinal center B cells, which represent the cell of origin for many B cell malignancies. Cd19-Cre-Hdac3−/− mice showed impaired germinal center formation along with a defect in plasmablast production. Analysis of Hdac3−/− germinal centers revealed a reduction in dark zone centroblasts and accumulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…Accordingly, the GC reaction in Tbl1xr1 LOF mice was significantly impaired, and GCB showed upregulation of BCL6 targets. Whereas Bcl6-KO completely abrogates GC formation (Hatzi and Melnick, 2014), Tbl1xr1 LOF effects are reminiscent of the milder effects observed in mice carrying NCOR/SMRT LOF mutations that disrupt interaction with HDAC3 (Jiang et al, 2017) or Hdac3 conditional deletion (Stengel et al, 2019). The difference in severity between BCL6 versus TBL1XR1/SMRT complex deficiency phenotype is likely due to SMRT/HDAC3-independent BCL6 functions such as interaction with BCOR and LSD1 (Hatzi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the GC reaction in Tbl1xr1 LOF mice was significantly impaired, and GCB showed upregulation of BCL6 targets. Whereas Bcl6-KO completely abrogates GC formation (Hatzi and Melnick, 2014), Tbl1xr1 LOF effects are reminiscent of the milder effects observed in mice carrying NCOR/SMRT LOF mutations that disrupt interaction with HDAC3 (Jiang et al, 2017) or Hdac3 conditional deletion (Stengel et al, 2019). The difference in severity between BCL6 versus TBL1XR1/SMRT complex deficiency phenotype is likely due to SMRT/HDAC3-independent BCL6 functions such as interaction with BCOR and LSD1 (Hatzi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…HDAC inhibitors gradually alter histone acetylation to change chromatin structure and impact gene expression. 49 , 50 These generally require chronic exposure over time to cause these downstream changes in gene expression levels leading to cell death. In contrast, the pharmacokinetics of intravitreal injection, 51 53 with single injections spaced out over weeks, and the rapid decline in vitreous drug levels following each injection, would not be thought to be conducive to this sort of chronic sustained change in gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Acetylation by Inhibiting HDAC3. It has been reported that HDAC3 activates the transcription of FOXO1 [22]. We proceeded in this study to investigate whether CDM induced FOXO1 acetylation by inhibiting HDAC3.…”
Section: Cdm Promotes Foxo1mentioning
confidence: 99%